The slippery slope - Snicket, Lemony (Snicket, Lemony. Series of unfortunate events, 2003)
In the perilous Mortmain Mountains, Klaus and Violet Baudelaire meet another well-read person, who helps them try to rescue Sunny from the villainous Count Olaf and his henchmen as they all near "the last safe place."